Numerical Design of a THz Metamaterial Biosensor for Early Skin and Breast Cancer Detection - Suhail Asghar Qureshi; Zuhairiah Zainal Abidin; Noor Azwan Shairi; Huda A Majid; Hongnian Yu; Nurul Bashirah Ghazali (International Journal of Integrated Engineering, 2026)
This paper presents a high-sensitivity terahertz (THz) metamaterial absorber engineered for early-stage detection of skin and breast cancers using a full-wave simulation approach. The proposed sensor employs a hybrid square-ring geometry, achieving a base absorption rate of 51% in the unloaded state. Upon dielectric loading with biological samples, the absorption rate significantly increases up to 99% for melanoma tissue and 98% for normal breast tissue. Dielectric properties of biological samples were modelled using the Double Debye model, enabling realistic simulation of tissue-specific spectral responses. The sensor exhibits measurable resonance frequency shifts up to 48 GHz between normal and malignant samples with peak sensitivity values of 5.2 GHz/µm for melanoma, 3.7 GHz/µm for basal cell carcinoma, and 1.7 GHz/µm for breast cancer. These shifts show a linear dependence on sample thickness, highlighting the potential for severity assessment. The findings establish a simulation-based foundation for non-invasive, label-free THz diagnostic systems with promising prospects for future clinical transformations.